Peripheral realism of Carlos Escudé - A. A. Eremin (Ибероамериканские тетради, 2021)
In this article the author analyzes a theoretical direction called “Peripheral Realism”, which has arisen within the scope of neorealism in 1990s due to an acknowledged Argentinean political scientist Carlos Escudé. The author makes an attempt to provide a complex analysis of the original theory of 1992 and compares it with the modern realities of international relations. The author also conducts a comparative analysis of the original theory and its revised version of 2016, in order to trace the dynamics of its development. The main objective of the study is to establish whether the theory of peripheral realism can be attributed to the so-called ‘non-Western’ theories of international relations. First of all, the article is based on an in-depth analysis of the theoretical basis of Carlos Escudé’s peripheral realism theory on the basis of his main writings of 1992 and 1995, as well as an analysis of subsequent variations of the theory in 2012 and 2015. The study also uses a comparative analysis method, which contrasts the features and theoretical positions of the canonical ‘grand’ theories of international relations (especially realism and neo-realism, being the origins for the theory) and correlates them with those of the theory of peripheral realism in order to highlight the role and place of this theory in the configuration of Western and non-Western theories of international relations. The author concludes that the uniqueness of the concept comes from assessing reality from the point of ‘weaker’ and developing countries, which is not generally customary for Anglo-Saxon theories. This unique feature puts the concept of peripheral realism beyond the perceptions of the nature of world politics generally accepted in the research community. The study was originally drafted for the research seminar “Non-Western Theories of International Relations” of the Department of theory and history of international relations of RUDN University, as well as for the joint research seminar of RUDN and HSE University “Non-Western Theories of International Relations in a Polycentric World.”